UAE-HPLC-UV: new contribution for fast determination of total isothiocyanates in Brassicaceae vegetables - Fusari Gómez, Cecilia Mara (2015)
Total isothiocyanates content (ITC) is considered a good indicator of bioactive compounds responsible for beneficial effects related to Brassicaceae vegetables. Analytical performance is a critical factor for routine analysis in plant tissues.The extraction technique for isolating phytochemicals fromBrassicaceae vegetables is currently the bottleneck of themethodology. The aimof this work was to optimize this step in the analytical process. Fast and less expensive alternative, based on ultrasound-assisted extraction technique (UAE) for direct extraction of GLS into an aqueous phase and further analysis of the hydrolysis product, was optimized. Full factorial (2) design followed by Central Composite Design (CCD) was used to obtain the optimum extraction conditions. Selected conditions were homogenization time (9 min); ultrasound bath time (5 min); and sample-to-solvent ratio (1 : 5 w/vmgmL−1). Theproposed analytical methodology exhibits satisfactory analytical performance in terms of linearity, precision (RSD < 2.4%), and limits of detection (26 nmol g−1 w.w.).Thenew analyticalmethodology was applied to cauliflower, cabbage, watercress, and broccoli samples with recoveries higher than 86%.TheUAE extraction technique was showed to be efficient for real samples analysis leading to sensible, selective, and reproducible methodology for ITC analysis.